Measuring theory of mind (ToM) with preschool-aged children: storybooks and observations with iPads. Issue 1 (2nd January 2023) - Ralph, Rachel; Code, Jillianne; Petrina, Stephen
ABSTRACT: Theory of Mind (ToM) is an individual's ability to understand the cognitive states of others, including their desires, beliefs, and knowledge. ToM describes how children, by the age of four, understand how others may be thinking or feeling. It is the ability to understand the thinking or viewpoints of their peers. This paper will describe ToM levels with preschool-aged children ( n  = 5). The current research used a storybook task battery to measure children's ToM, as well as developed observational measures, focused on three domains from the task battery. Results of this exploratory study indicate that three of the children had a high level of ToM while the other two were low, as they were not of age. Results also indicate that ToM was observed but challenging to measure as it is primarily an internal process. Future studies can use these suggested tools in conjunction to get a better understanding of ToM with groups preschool-aged children.